2015
DOI: 10.5120/20070-1989
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mean Median Filter for Noise and Artifacts Suppression from Digital Images

Abstract: A novel mean-median filter is proposed for the suppression of impulse noise and various artifacts from the digital images. Leading Diagonal Sorting Algorithm is used with the fixed 3x3 size working window to compute the median. Truncated mean is computed by defining the boundaries and truncating the pixel values in the filtering window that fall outside the defined boundary. Noise detection is carried in two steps: In the first step the 'reference pixel' is tested for the presence of impulses with Min-Max dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It has been observed that the window sizes needed for 10% to 90% noise density range between 3 to 9. Table 2 shows the better performance of the proposed NAF over the filter schemes described in [12], [17], [18] and [22] for low to high noise density cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the window sizes needed for 10% to 90% noise density range between 3 to 9. Table 2 shows the better performance of the proposed NAF over the filter schemes described in [12], [17], [18] and [22] for low to high noise density cases.…”
Section: Resultsmentioning
confidence: 99%
“…A Novel Median Filter (NMF) presented in [22] addresses the task of impulsive noise cleaning from the noisy grey scale images and aims at effectively suppressing the impulse noise while preserving the edge information intact. Proposed scheme is simple and yields better denoising performance with better detail preserving up to 60-70% noise densities, but fails to perform well at higher noise situations.…”
Section: Introductionmentioning
confidence: 99%